Mixed solvency concept in reducing surfactant concentration of selfâ€emulsifying drug delivery systems of candesartan cilexetil using Dâ€optimal mixture design - Chandan, Chandna; RK, Maheshwari (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of this present study was to explore the utility of â€œmixed solvencyâ€ concept to enhance the solubility of poorlyâ€water soluble drug, candesartan cilexetil (CC) in modified solubilizer system. The objective of this paper is to reduce the surfactant concentration traditionally involved in the formulation of selfâ€emulsifying drug delivery systems (SEDDS) by proposing an alternate system of solubilizer to provide novel surfactant/cosurfactant system, to aid traditionally involved components in the formulation of SEDDS.The present study showed that â€œmixed solvencyâ€ concept was successfully employed in solubility enhancement of CC in (Transcutol P: B3Mix [1:1]) up to 303 mg/g of blend. Present study demonstrated the promising use of â€œmixed solvencyâ€ concept in solubility enhancement of poorlyâ€water soluble drugs and tool to reduce the net surfactant concentration employed in designing of SEDDS.